2004
DOI: 10.1093/aje/kwh180
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Bleeding during Pregnancy and Preterm Birth

Abstract: This study investigated the relation between self-reported vaginal bleeding during pregnancy and preterm birth in a prospective cohort of 2,829 pregnant women enrolled from prenatal clinics between 1995 and 2000 in central North Carolina. The overall association between vaginal bleeding and preterm birth was modest (risk ratio (RR) = 1.3, 95% confidence interval (CI): 1.1, 1.6). Bleeding in the first trimester only was associated with earlier preterm birth (< or =34 weeks' gestation) (RR = 1.6, 95% CI: 1.1, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
57
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 23 publications
17
57
1
6
Order By: Relevance
“…Yang et al found that of 683 women enrolled in a prospective study who reported vaginal bleeding in the first or second trimester, half delivered at less than 36 weeks. 13 Women experiencing bleeding had a 17.3% rate of prior preterm birth, similar to our 21% rate, but the authors did not report causes of bleeding or hospitalization rate, and they excluded multiple gestations. 13 Bleeding was documented by telephone interview only.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Yang et al found that of 683 women enrolled in a prospective study who reported vaginal bleeding in the first or second trimester, half delivered at less than 36 weeks. 13 Women experiencing bleeding had a 17.3% rate of prior preterm birth, similar to our 21% rate, but the authors did not report causes of bleeding or hospitalization rate, and they excluded multiple gestations. 13 Bleeding was documented by telephone interview only.…”
Section: Discussionsupporting
confidence: 71%
“…13 Women experiencing bleeding had a 17.3% rate of prior preterm birth, similar to our 21% rate, but the authors did not report causes of bleeding or hospitalization rate, and they excluded multiple gestations. 13 Bleeding was documented by telephone interview only. 13 In another cohort of women in the United States, only 10 of 92 women with second trimester bleeding delivered between 34 and 36 weeks, and four delivered at less than 34 weeks.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations